2015
DOI: 10.1507/endocrj.ej15-0125
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial dysfunction, insulin resistance and inflammation in congenital hypogonadism, and the effect of testosterone replacement

Abstract: Patients with hypogonadism not only present with poor libido, loss of energy, muscle atrophy and depression but also with chronic metabolic disorders such as dyslipidemia, obesity, hypertension and type 2 diabetes mellitus (T2DM) [1][2][3] and increased mortality [4]. The dysmetabolic features of hypogonadism are present even in the very young age, in patients with congenital hypogonadotrophic hypogonadism (CHH) [5].Endothelial dysfunction, insulin resistance and inflammation in congenital hypogonadism, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 50 publications
3
14
0
Order By: Relevance
“…However, plasma ADMA levels did not improve but worsened after TRT in our homogenous study population. This is in accordance with our previous report of a similar follow-up study in a CHH population [20]. The mechanism of this increase in ADMA levels after TRT is not clear.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…However, plasma ADMA levels did not improve but worsened after TRT in our homogenous study population. This is in accordance with our previous report of a similar follow-up study in a CHH population [20]. The mechanism of this increase in ADMA levels after TRT is not clear.…”
Section: Discussionsupporting
confidence: 90%
“…Most of these studies showing adverse effects of TRT were by and large performed on frail elderly populations with several confounders. However, we also reported endothelial dysfunction, inflammation and insulin resistance after TRT in unconfounded, young hypogonadal patients [18][19][20]. To our knowledge, the present study is the first to search for the effect of TRT on 25(OH)D3 and FGF-23 levels .…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Because TWEAK is a subgroup of TNFSF that is synthesized by Th1 lymphocytes, we consider that TWEAK may play role in increased autoimmune response. Indeed, a number of previous studies showed that TWEAK was associated with etiopathogenesis of several autoimmune diseases (systemic lupus erythematosus (SLE), multiple sclerosis, type 1 diabetes mellitus etc) [6,7]. However, it is not known whether TWEAK has a role in the etiopathogenesis of HT, which is an autoimmune disease.…”
Section: Introductionmentioning
confidence: 99%